MODEL PEMBELAJARAN LANGSUNG BERBASIS PROYEK TERHADAP HASIL BELAJAR KONSEP PERUBAHAN WUJUD BENDA PADA PESERTA DIDIK TUNARUNGU PADA SMPLB - PRABOWO, BUDIANTO (Jurnal Pendidikan Khusus, 2017)
Abstract: The education of hearing impairment children, especially in intellectual ability, had difficulty in understanding a concept especially change of substance concept. The project based learning trained and accustomed the hearing impairment children to be competent to think and autonomous in solving a problem and also assignment meaningfully. This reaserch purpose was to enhance the learning result of change of substance concept to hearing impairment children throught project based learning. This research method used quantitative approach with pre experiment kind and the arrangement of “One Group Pretest – Posttest Design”. The result of data analysis obtained was Zh greater than Z table i.e. 2,20 > 1,96 so that Ho was refused and Ha was accepted. It mean there was influence of using project based learning toward learning result of change of substance concept to the eigth class fo hearing impairment children SMPLB-B Pertiwi Mojokerto.   Keywords: Project Based Learning, Learning Result